2008
DOI: 10.1593/neo.07869
|View full text |Cite
|
Sign up to set email alerts
|

A Pathologic Link between Wilms Tumor Suppressor Gene, WT1, and IFI16

Abstract: The Wilms tumor gene (WT1) is mutated or deleted in patients with heredofamilial syndromes associated with the development of Wilms tumors, but is infrequently mutated in sporadic Wilms tumors. By comparing the microarray profiles of syndromic versus sporadic Wilms tumors and WT1-inducible Saos-2 osteosarcoma cells, we identified interferon-inducible protein 16 (IFI16), a transcriptional modulator, as a differentially expressed gene and a candidate WT1 target gene. WT1 induction in Saos-2 osteosarcoma cells le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…For reasons that remain unclear, Wilms tumors appear very resistant to establishment as long-term cultures, and several early models such as SK-NEP-1 and G401 have later been proven to be tumors other than Wilms (10,11). In the present study, we have used a small panel of more recently described Wilms tumor cell lines derived from primary in vitro culture [17.94 (12), WT-CLS1 (13), CCG 99-11 (14), STA2A (15) We addressed the lack of in vitro preclinical data by studying the effect of targeting the IGF1R in these models by genetic and pharmacological means. We demonstrated that the small-molecule inhibitor NVP-AEW541 had a potent cytotoxic effect against Wilms tumor cells in vitro through down-regulation of PI3K and MAPK pathways, as well as cell cycle control genes such as CCNA2 and CCNB1, leading to a marked G 1 arrest and subsequent induction of apoptosis in a caspase-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…For reasons that remain unclear, Wilms tumors appear very resistant to establishment as long-term cultures, and several early models such as SK-NEP-1 and G401 have later been proven to be tumors other than Wilms (10,11). In the present study, we have used a small panel of more recently described Wilms tumor cell lines derived from primary in vitro culture [17.94 (12), WT-CLS1 (13), CCG 99-11 (14), STA2A (15) We addressed the lack of in vitro preclinical data by studying the effect of targeting the IGF1R in these models by genetic and pharmacological means. We demonstrated that the small-molecule inhibitor NVP-AEW541 had a potent cytotoxic effect against Wilms tumor cells in vitro through down-regulation of PI3K and MAPK pathways, as well as cell cycle control genes such as CCNA2 and CCNB1, leading to a marked G 1 arrest and subsequent induction of apoptosis in a caspase-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the activation of p53 in cells increases levels of the IFI16 protein through transcriptional mechanisms, we transfected Saos Pro72 or Saos Arg72 cells with IFI16-luc-reporter plasmid in which transcription of the luciferase reporter gene is driven by the 5 ¶-regulatory region (1.68 kb) of the IFI16 gene (31). As shown in Fig.…”
Section: Functional P53 Activates Transcription Of the Ifi16 Genementioning
confidence: 99%
“…In cell culture systems WT1 generally acts as a growth suppressor (13)(14)(15)(16)(17)(18) but its overexpression in a number of tumor types such as colon and thyroid (19,20) suggests that it may act as an oncogene as well. Accordingly knockdown of WT1 led to decreased growth of a Wilms tumor cell line suggesting a permissive role in growth in some cases of Wilms tumor (21).…”
mentioning
confidence: 97%
“…WT1 target genes include CDKN1A (22), a negative regulator of the cell cycle; AREG (23), a facilitator of kidney differentiation; WNT4 (24), a stimulator of renal development; and SPRY1 (25), a critical intracellular regulator of receptor tyrosine kinase signaling and kidney development. Examination of gene expression in WT1 null and WT1 replete Wilms tumor specimens identified a gene (IFI16) not normally regulated or even expressed in the same subcellular compartment as WT1 but regulated in a pathological manner in tumors (21).…”
mentioning
confidence: 99%